Our transatlantic flight - Alcock, John, Sir, 1892-1919 (Kimber, 1969)
Our Transatlantic Flight Introduction / by Captain John Alcock -- My transatlantic flight / by Sir John Alcock -- Flying the Atlantic in sixteen hours / by Sir Arthur Whitten Brown. Introduction / by Lord Northcliffe -- Flying the Atlantic in sixteen hours -- St. John's -- The start -- Evening -- Night -- Morning -- The arrival -- Aftermath of arrival -- The navigation of aircraft -- The future of transatlantic flight -- The air age -- As it seemed afterwards / by Captain John Alcock -- Earlier venture. Our Atlantic attempt / by H.G. Hawker -- Appendix. The Rolls Royce engine